THE GLOBAL IMPORTANCE AND RELEVANCE OF ADDRESS FORMS IN EDUCATION - Kasimova Dilfuza Djurayevna (Bright Mind Publishing, 2026)
This article examines the global importance and relevance of address forms in education, emphasizing their role in shaping communication, social relationships, and cultural identity within educational settings. Address forms—such as titles, honorifics, first names, and kinship terms—serve not only as linguistic tools but also as markers of respect, hierarchy, and social distance. In an increasingly globalized world, educational institutions bring together individuals from diverse linguistic and cultural backgrounds, making the appropriate use of address forms crucial for effective communication and mutual understanding. The article explores theoretical perspectives, cultural variations, and practical implications of address forms in classrooms, highlighting their influence on teaching effectiveness, student engagement, and intercultural competence.
Keywords: Forms of address, education, sociolinguistics, intercultural communication, politeness theory, classroom discourse, teacher-student interaction, global education, cultural identity.